DETERMINAN DAYA SAING WISATA KULINER NGERANGAN KLATEN - Agusetyaningrum, Theresia; Sumastuti, Efriyani; Violinda, Qristin (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
This study began because the level of visits to Ngerangan Klaten culinary tourism was less than other culinary tours in Klaten Regency and the findings that the variables that determined competitiveness obtained different results which then led to the formulation of the problem of "how to improve competitiveness".Departing from the formulation of the problem, this study aims to determine the effect of asset management, business capital, business age, financial literacy, and innovation on the competitiveness of Klaten Ngerangan culinary tourism. This study uses probability sampling technique with simple random sampling method. Data analysis in this study used the Statistical Package for the Social Sciences (SPSS) program. The results of the analysis and discussion show that asset management variables have no effect on competitiveness, business capital variables have no effect on competitiveness, business age variables have no effect on competitiveness, financial literacy affects competitiveness, and innovation affects competitiveness